2017
DOI: 10.1177/0020764017744581
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of married immigrant women in South Korea and its risk and protective factors: A literature review

Abstract: With the paucity of prospective studies, longitudinal research is needed that addresses the long-term processes of married immigrant women's psychological adaptation and the underlying risk and protective factors at diverse settlement phases. Furthermore, we suggest that future research should focus on how women's personal attributes interact with macro-level, socio-cultural contexts, including familial relationship and the community social-support system. Future evidence-based policy and interventions should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
(109 reference statements)
2
20
0
Order By: Relevance
“…A study by Mangalore and Knapp also reported similar findings with mental health across various ethnicities in the UK [12]. The role of income on immigrants is, however, not clear in South Korea, as shown in a recent review [6]. The review identified key risk factors that influenced mental health of married immigrant women in South Korea.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A study by Mangalore and Knapp also reported similar findings with mental health across various ethnicities in the UK [12]. The role of income on immigrants is, however, not clear in South Korea, as shown in a recent review [6]. The review identified key risk factors that influenced mental health of married immigrant women in South Korea.…”
Section: Introductionmentioning
confidence: 78%
“…The Korean Wind phenomenon, a massive return-migration of ethnic Koreans in China beginning in the early 1990s, made these campaigns possible. International marriage brokers have then facilitated this type of marriage, especially in the mid-2000s, leading to a shift from ‘coethnic international marriages’ to ‘interethnic international marriages’, with women mostly from China, and more recently from Southeast Asian countries such as Vietnam and the Philippines [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Immigrant women faced dual burdens as foreign wives: acculturation and rapid change in family roles. Furthermore, they are exposed to multiple social risks, such as social isolation and violence [ 53 ]. Marriage satisfaction and social support are protective factors for immigrant women to address the burden that foreign wives experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, although this type of intervention is sufficient, the role of the partner is a lot bigger in resilience. The degree of respect, acceptance, and attention received from others who are considered to be meaningful has the most significant impact on the development of self-esteem [45]. Since their Korean spouses are usually the most important and meaningful people to marriage immigrant women, being recognized, respected, and rewarded by the spouse and building a strong supportive relationship with them decreases the resilience process time and leads the women to a high level of growth.…”
Section: Discussionmentioning
confidence: 99%
“…As such, partner intervention regarding fostering a positive marital relationship and its fees should be addressed at the system level. Moreover, family educational programs should be provided to promote egalitarian spousal relationships and prevent domestic violence [45].…”
Section: Discussionmentioning
confidence: 99%